2010
DOI: 10.1007/s11356-010-0349-4
|View full text |Cite
|
Sign up to set email alerts
|

Major and trace elements in soils in the Central Pyrenees: high altitude soils as a cumulative record of background atmospheric contamination over SW Europe

Abstract: None of the storage capacity properties of soils examined were determinant of the differences in elemental concentrations along the altitudinal transect. At the upper altitude range, Ni, Cu, and Pb showed a approximately two- to fivefold increase over the average concentration of the local dominant lithology, reflecting the regional and global background of atmospheric contamination in the area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 46 publications
3
18
0
Order By: Relevance
“…This atmospheric contamination is detectable in the sediments of most Pyrenean lakes (Camarero, 2003) and in soils even at the highest altitudes (Bacardit and Camarero, 2010b). In the case of Pb, we have shown that such contamination has existed since ancient times (Camarero et al, 1998).…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…This atmospheric contamination is detectable in the sediments of most Pyrenean lakes (Camarero, 2003) and in soils even at the highest altitudes (Bacardit and Camarero, 2010b). In the case of Pb, we have shown that such contamination has existed since ancient times (Camarero et al, 1998).…”
Section: Introductionmentioning
confidence: 68%
“…The proportion of trace metals in the fraction extracted with our acid extraction was compared with the total content analysed with an energy-dispersive multielement analyser (EMMA) miniprobe XRF analyser (Cheburkin and Shotyk, 1996) in several test soil samples (Bacardit and Camarero, 2010b). Total Al and Ti were measured by conventional XRF at the University of Heidelberg analytical services.…”
Section: Sample Preparation and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on soil background concentrations of trace (Salonen and Korkka-Niemi, 2007;Biondi et al, 2011;Preston et al, 2014;Alfaro et al, 2015) and major elements (Montserrat and Camarero, 2010;Hannan and Tanguma, 2012;Dantu, 2014) are easily found in the literature. However, data regarding REEs are comparatively scarce and have mainly focused on determination of REEs in a limited number of soil types (Turra et al, 2011;Damascena et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The elevated levels of As are likely partially due to the naturally high concentrations of As occurring in the local bedrock. Bacardit and Camarero (2010) found that geogenic As can occur in “hotspots.” The elevated levels may also be caused by past spills or the use or disposal of treated wood products (Guney et al, 2010).…”
Section: Discussionmentioning
confidence: 99%